2010
DOI: 10.1111/j.1439-0531.2010.01684.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an Antral Follicle–like Structure of Bovine Cumulus–Oocyte Complexes Embedded Individually or in Groups in Collagen Gels

Abstract: Culture techniques of antral follicle-like structure (AFLS) derived from cumulus-oocyte complexes (COCs) might provide important insights into follicular development and oocyte maturation. This study was undertaken to investigate the effects of embedding bovine COCs individually (one COC) or in groups (4-5 COCs) in collagen gels on the formation of AFLS and the meiotic status of oocytes. The observations of AFLS formation were performed every second day for 14 days. The AFLS was formed at Day 2 or 4 after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In a previous study, we observed that almost all oocytes had undergone the GVBD stage, irrespective of AFLS formation, when GV-stage oocytes with unknown oocyte diameter from follicles 1 to 5 mm in diameter were cultured for 14 days in collagen gel (Abakushina et al, 2011). In the present study, similarly, COCs aspirated from follicles 1-5 mm diameter were cultured for 8 days using the same culture method.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In a previous study, we observed that almost all oocytes had undergone the GVBD stage, irrespective of AFLS formation, when GV-stage oocytes with unknown oocyte diameter from follicles 1 to 5 mm in diameter were cultured for 14 days in collagen gel (Abakushina et al, 2011). In the present study, similarly, COCs aspirated from follicles 1-5 mm diameter were cultured for 8 days using the same culture method.…”
Section: Discussionmentioning
confidence: 79%
“…The aim of this experiment was to evaluate the effect of dbcAMP on the formation of the AFLS and on the meiotic status of oocytes cultured for 8 days. In a previous study, we found that the mean diameters of AFLS in the group culture method were smaller than those in the individual culture method, but more COCs formed AFLS in the group culture method (Abakushina et al, 2011). Therefore, the COCs were embedded in collagen gels by the group culture method (3 COCs per gel) and then cultured in TCM199 culture medium supplemented with 0.5, 1.0 or 2.0 mM of dbcAMP (Sigma-Aldrich) for 8 days.…”
Section: Hormonal Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The diameters of oocytes with AFLS formation were measured before and after growth culture for 8 days. The meiotic stage in the oocytes were analyzed by staining with the DNA-binding fluorochrome bisbenzimide (Hoechst 33342) that was previously described by Abakushina et al (9).…”
Section: Methodsmentioning
confidence: 99%